Engaged : Mr. and Mrs. W.E. Savage (1983)
Article on the engagement of Lynn Savage and Jerry Don Kehoe.
Master List item # 5
File location is in the Raton File Cabinet
Keywords: Savage, W.E.; Savage, W.E. (Mrs.); Savage, Lynn; Kehoe, Jerry Don; Kehoe, Alta; Kehoe, Pat; First United Methodist Church; Sanford-Fritch High School; Seward County Community College; Amarillo College; Springer High School; Phillips Petroleum Company; Engagement; Vows; Fritch, Texas; Cimarron, New Mexico; Las Cruces, New Mexico; Liberal, Kansas; Amarillo, Texas; Springer, New Mexico